Nutrient Contents of the Freshwater Crab, Isolapotamon bauense from Sarawak, Malaysia (Borneo) - Jongkar, Grinang; Pang, Sing Tyan; Andrew Alek, Tuen; Das, I. (Universiti Sains Malaysia, 2017)
Data on nutrient contents of freshwater crabs are important for ecological studies and species conservation assessments, especially when the species concerned is threatened among others by habitat destruction and uncontrolled resources utilisation. Indeed comprehensive biological information is required to reconcile the needs between sustainable resources utilisation and conservation of the species. This study documents the nutrient contents of a freshwater crab, Isolapotamon bauense which is listed as ‘Vulnerable’ in the IUCN Red List of Threatened Species and also being harvested by local community for dietary supplement. Results show that muscles of the freshwater crab contain a substantial amount of nutrients in particular water content (male = 79.31 ± 2.30 %, female = 77.63 ± 0.56 %), protein (male = 77.47 ± 6.11 %, female = 63.28 ± 3.62 %), magnesium (male = 51.48 ± 16.10 mg/g, female = 39.73 ± 6.99 mg/g) and calcium (male = 25.50 ± 6.98 mg/g, female = 39.73 ± 6.99 mg/g). Means of nutrient contents between male and female crabs are not significantly different. It is estimated that an individual of I. bauense with weight range of 56–139 g contained on average of 0.35 ± 0.15 g of protein. Our estimation also shows that the number of individuals of the freshwater crab required to meet the recommended daily protein intakes of the community concerned is in the range 35–96 individuals for children, 130–188 individuals for adolescents, 171–179 individuals for men and 149–159 individuals for women. The results imply that harvesting of wild I. bauense as a source of protein supplement naturally may not be practical because of its relatively low population abundance, and conservation of the species for its ecological roles may thus be preferred.